Peningkatan Motivasi Belajar Akuntansi dan Kemandirian dalam Manajemen Keuangan - Siti Munawaroh; Mely Marsanda; Djupiansyah Ganie; Darmono Darmono; Agus Purwoko; Rustam Rustam; Margusianti Margusianti; Nanda Dwi Saputri (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Learning motivation and independence in financial management are two crucial aspects in developing the competencies of vocational high school students, particularly in accounting. This study aims to identify strategies to increase motivation to learn accounting and foster financial independence in students at SMKN 7 Berau. Through an interactive and contextual learning approach, students are encouraged to understand accounting concepts in an applied way and manage their personal finances responsibly. The results of the activity indicate increased active participation, deeper conceptual understanding, and students' ability to prepare budgets and record simple transactions. These findings indicate that integrating experiential learning methods and gamification can be an effective solution for increasing student motivation and independence in financial matters. This research contributes to the development of a more relevant accounting learning model that has a direct impact on students' readiness to face future economic challenges.